The Perspective of Dysregulated LncRNAs in Alzheimer's Disease: A Systematic Scoping Review - Asadi, Mohammad Reza; Hassani, Mehdi; Kiani, Shiva; Sabaie, Hani; Moslehian, Marziyeh Sadat; Kazemi, Mohammad; Ghafouri-Fard, Soudeh; Taheri, Mohammad; Rezazadeh, Maryam (Frontiers in Aging Neuroscience, 2021)
LncRNAs act as part of non-coding RNAs at high levels of complex and stimulatory configurations in basic molecular mechanisms. Their extensive regulatory activity in the CNS continues on a small scale, from the functions of synapses to large-scale neurodevelopment and cognitive functions, aging, and can be seen in both health and disease situations. One of the vast consequences of the pathological role of dysregulated lncRNAs in the CNS due to their role in a network of regulatory pathways can be manifested in Alzheimer's as a neurodegenerative disease. The disease is characterized by two main hallmarks: amyloid plaques due to the accumulation of β-amyloid components and neurofibrillary tangles (NFT) resulting from the accumulation of phosphorylated tau. Numerous studies in humans, animal models, and various cell lines have revealed the role of lncRNAs in the pathogenesis of Alzheimer's disease. This scoping review was performed with a six-step strategy and based on the Prisma guideline by systematically searching the publications of seven databases. Out of 1,591 records, 69 articles were utterly aligned with the specified inclusion criteria and were summarized in the relevant table. Most of the studies were devoted to BACE1-AS, NEAT1, MALAT1, and SNHG1 lncRNAs, respectively, and about one-third of the studies investigated a unique lncRNA. About 56% of the studies reported up-regulation, and 7% reported down-regulation of lncRNAs expressions. Overall, this study was conducted to investigate the association between lncRNAs and Alzheimer's disease to make a reputable source for further studies and find more molecular therapeutic goals for this disease.